Influence of weight gain on the modulation of wound healing following tooth extraction - Furuse, Cristiane [UNESP]; Almeida, Aline F.; Costa, Sidnei F. [UNESP]; Ervolino-Silva, Ana C. [UNESP]; Okamoto, Roberta [UNESP]; Sumida, Doris Hissako [UNESP]; Matsumoto, Mariza Akemi [UNESP]; Leite, Fábio R.M. (Elsevier, 2018)
Introduction: Obesity is characterized by extreme body fat accumulation related to lean body mass. The low–grade systemic inflammation induced by weight gain may influence wound healing. This study assessed the association between obesity and alveoli repair after tooth extraction. Methods: Forty-two male Wistar rats were randomly divided into two groups: weight gain (n = 21), animals fed with hyperlipidic cafeteria diet in order to gain weight; and control (non-obese; n = 21) regularly fed rats. After twelve weeks, the upper right central incisor was extracted and animals were sacrificed after 7, 14 and 28 days. Slides were obtained for histological analysis. Bone formation and protein expression at the different periods were compared using Kruskal-Wallis test and Dunn post-test. Results: Bone area was higher in the control group all over the experiment with more TRAP-positive cells and TRAP-positive labeling in the weight gain group. RANKL was homogeneously expressed along the experiment with no differences among the groups; conversely OPG levels reduced in the weight gain groups 14 and 28 days after tooth extraction. Osteocalcin labeling was higher in the control group after 7 days of extraction, with no differences at later time points. VEGF labeling was higher in the control group after 14 days of tooth extraction while the strongest immunolabeling in the weight gain group was observed 21 days post-extraction. Conclusion: Weight gain induced a delay in bone repair after tooth extraction. The increase in the number of TRAP-positive cells observed in the extraction site seems to be mediated by the reduction in the expression of OPG rather than an overexpression of RANKL. In addition, the late expression of VEGF in the weight gain group might have delayed osteoblast migration and differentiation.
Keywords: Immunohistochemistry; Obesity; Repair; Tooth extraction